A Single Lung Transplant in a Patient with Fabry Disease: Causality or Far-Fetched? A Case Report - Martina Gaggl; Renate Kain; Peter Jaksch; Dominik Haider; Gerald Mundigler; Till Voigtländer; Raute Sunder-Plassmann; Paulus Rommer; Walter Klepetko; Gere Sunder-Plassmann (Case Reports in Transplantation)
Introduction. Fabry disease is a rare X-linked lysosomal storage disorder, characterized by an α-galactosidase A deficiency resulting in globotriaosylceramide storage within cells. Subsequently, various organ systems are involved, clinically the most important are kidneys, the heart, and the peripheral and central nervous systems. Although obstructive lung disease is a common pathological finding in Fabry disease, pulmonary involvement is a clinically disregarded feature. Case Presentation. We report a patient with a diagnosis of chronic obstructive pulmonary disease (COPD) who received a single lung transplant in 2007. Later, a kidney biopsy revealed the diagnosis of Fabry disease, which was confirmed by enzymatic and genetic testing. Ultrastructural changes in a native lung biopsy were consistent with the diagnosis. Although the association of a lung transplant and Fabry disease appears far-fetched on first sight, respiratory impairment cannot be denied in Fabry disease. Conclusion. With this case presentation, we would like to stimulate discussion about rare differential diagnoses hidden beneath widespread disease and that a correct diagnosis is the base of an optimal treatment strategy for each patient. Overall, the patient might have benefited from specific enzyme replacement therapy, especially in view of the chronic kidney disease.